"Landmark" Articles in Female Pelvic Medicine and Reconstructive Surgery: Do We Read What We Cite?. Issue 1 (January 2021) - Gupta, Ankita; Kennedy, Bridget; Meriwether, Kate V.; Hobson, Deslyn T. G.; Francis, Sean L.; Stewart, J. Ryan
Abstract : Objective: The aim of the study was to describe the provision of a "landmark" article reading list to trainees by their Female Pelvic Medicine & Reconstructive Surgery (FPMRS) fellowship programs. Methods: In this cross-sectional study, a web-based survey was sent to program coordinators of accredited FPMRS programs. Available reading lists were collected, and a master list compiled. Nonparametric tests were used to investigate the association between the number of faculty members and presence of a reading list. Results: We received a response from 46 (92%) of the 50 Accreditation Council for Graduate Medical Education programs contacted. Half the programs (23/46, 50%) reported that they do not offer a recommended reading list, 5 programs were unsure and over more than 60% with a list (12/18, 67%) shared their list with the investigators. Programs had between 2 and 14 core faculty members with a median (interquartile range) of 4 (3–6). Programs with a reading list had significantly fewer faculty members (3.5, 3–5 vs 5, 3–6, P = 0.03). There were 323 unique articles across the 12 lists, with a median of 25 articles per list. Thirty-four articles were on 4 or more lists; 9 of these (9/34, 26%) have previously been identified as citation classics. Conclusions: At least 50% of the Accreditation Council for Graduate Medical Education accredited programs do not provide their fellows with a recommended reading list, and fewer core faculty members are associated with the presence of such a list. Although some commonalities are found between reading lists, a universal reading list of "landmark" articles could improve the consistency of FPMRS fellowship education.